The Implications of Nonmarketable Income for Consumption-Based Models of Asset Pricing - Brown, David P. (Journal of Finance, 1988)
A new representation of nonmarketable (NM) income is introduced in this essay. Using this representation and continuous trading, there exists a set of individuals who do not participate in the asset market and who consume at the rate of nonmarketable income derived from human capital. Because these individuals remain nonparticipants for a range of stochastic processes governing the NM income, consumption betas are not generally unique in value and the consumption-based CAPM (CCAPM) does not obtain. However, the intertemporal CAPM (ICAPM) of Merton remains valid.